PLANNING AND CONTROLLING OF BOTTLE TEA PRODUCTION USING ARTIFICIAL NEURAL NETWORKS AND FUZZY LINEAR PROGRAMMING - Sriwana, Iphov Kumala (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Planning and controlling of production is one of main activity in every industry including bottled tea industry. Planning and control enabled the industry to determine how many bottle tead must be produced, how many workers needed, how many stock should be kept and how much cost spent (production cost, stock cost, worker cost and overtime cost). In order to do this a prediction must be created. One of methods that may be used is by using artificial neural networks that the performance of the networks is valued by root value from the average of Root Mean Square Error/RMSE. Production planning and controlling of bottled tea, until now is made based on problem function that has a certain limit. In fact, there are many factors that may influence the problem function therefore decreasing accuracy.. This paper discusses an alternative solution of production planning with a model in linear fuzzy programming. Results show RMSE value at 0.0399 and value of λ 0.4994803.